A Cartesian Slab Based Multiblocking Strategy for Irregular Cylindrical Surfaces. (2017) - Mukherjee, Nilanjan; Makem, Jonathan E.
Abstract: Cylindrical surfaces of many irregularities populate aerospace and automotive engine components. Many of these surfaces represent power transmitting shafts and rotary mating parts that require structured meshes to expedite contact and other finite element analyses with their mates. This poses a challenge to surface and volume mesh generators. In this paper a novel method of multiblocking based on 2D Cartesian slabs is proposed for the generation of predominantly structured meshes on irregular cylindrical surfaces. A seam generation technique comprises the first step, leading to the creation of an axial line of optimal length to split the 3D surface to facilitate 2D flattened or parametric space generation. The 2D parametric domain of the surface is next transformed to an axis-parallel local coordinate system for Cartesian slab generation. An intricate virtual face split operator is used to dissect the 2d parameter space into parallel rectangular slabs of uniform or varying thicknesses. A light-weight, mesher-native topology builder that uses virtual topological elements is proposed for constructing a virtual topology network of the slabs. Results demonstrate high quality, high fidelity transfinite-dominant meshes on a host of trimmed cylindrical surfaces.